Dermal Delivery of Korean Red Ginseng Extract: Impact on Storage Stability of Different Carrier Systems and Evaluation of Rg1 and Rb1 Skin Permeation Ex Vivo - Klang, Victoria; Schweiger, Eva-Maria; Strohmaier, Simone; Walter, Verena Ina; Dekic, Zorana; Tahir, Ammar (Pharmaceutics, 2022)
The root extract of Panax ginseng C.A. Meyer (Korean red ginseng/KRG extract) is a traditional Asian remedy introduced to dermal products for its antioxidative potential. However, little is known about technological aspects or skin penetration of main ginsenosides. Thus, stable oil-in-water nanoemulsions (NEs) and hydrogels for dermal delivery of KRG extract were developed and characterised using light scattering methods, analysis of flow properties and pH measurements. In addition, Rg1 and Rb1 contents were monitored by UHPLC/MS. Different surfactants (phosphatidylcholine, monoacylphosphatidylcholine and polysorbate 80) and polymers (polyacrylic acid and hydroxyethylcellulose) were tested and compared for their compatibility with KRG extract. The results showed that incorporation of KRG extract led to a significantly reduced formulation pH in hydroxyethylcellulose gels (−22%), NEs (−15%) and carbomer gels (−4–5%). The dynamic viscosity was in the range of 24–28 Pas at 10 s−1 for carbomer gels. The highest storage stability and skin permeation were observed for a hydroalcoholic gel with carbomer 50,000 and TRIS buffer (each of 1% w/w), containing ethanol (20% w/w) and KRG extract (2% w/w). Ex vivo diffusion cell studies confirmed skin permeation of the moderately lipophilic Rg1, but not the more hydrophilic Rb1 with a larger molecular weight.